2009
DOI: 10.1007/s11104-009-9895-2
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of phosphorus and nitrogen in the rhizosphere and plant growth promotion by microorganisms

Abstract: International audienceThe rhizosphere is a complex environment where roots interact with physical, chemical and biological properties of soil. Structural and functional characteristics of roots contribute to rhizosphere processes and both have significant influence on the capacity of roots to acquire nutrients. Roots also interact extensively with soil microorganisms which further impact on plant nutrition either directly, by influencing nutrient availability and uptake, or indirectly through plant (root) grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
827
1
56

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,509 publications
(906 citation statements)
references
References 366 publications
(323 reference statements)
22
827
1
56
Order By: Relevance
“…mycorrhizal associations) or by hormonal stimulation of root growth, branching, or root hair development (phytostimulation; e.g. production of indole-3-acetic acid, GAs, or enzymes that alter plant ethylene precursors, such as 1-aminocyclopropane-1-carboxylate deaminase; Richardson et al, 2009a;Hayat et al, 2010); (2) alteration of sorption equilibria that may result in increased net transfer of orthophosphate ions into soil solution or facilitate the mobility of organic P either directly or indirectly through microbial turnover (Seeling and Zasoski, 1993); and (3) through induction of metabolic processes that are effective in directly solubilizing and mineralizing P from sparingly available forms of soil inorganic and organic P ( Fig. 1; Richardson et al, 2009a).…”
Section: Mechanisms Of P Mobilization By Soil Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…mycorrhizal associations) or by hormonal stimulation of root growth, branching, or root hair development (phytostimulation; e.g. production of indole-3-acetic acid, GAs, or enzymes that alter plant ethylene precursors, such as 1-aminocyclopropane-1-carboxylate deaminase; Richardson et al, 2009a;Hayat et al, 2010); (2) alteration of sorption equilibria that may result in increased net transfer of orthophosphate ions into soil solution or facilitate the mobility of organic P either directly or indirectly through microbial turnover (Seeling and Zasoski, 1993); and (3) through induction of metabolic processes that are effective in directly solubilizing and mineralizing P from sparingly available forms of soil inorganic and organic P ( Fig. 1; Richardson et al, 2009a).…”
Section: Mechanisms Of P Mobilization By Soil Microorganismsmentioning
confidence: 99%
“…Gerretsen (1948) showed that pure cultures of soil bacteria could increase the P nutrition of plants under controlled conditions through solubilization of precipitated forms of calcium (Ca) phosphates. Since this study, many examples of microbially mediated P mobilization and characterization of different microorganisms have been reported (for review, see Richardson, 2001;Gyaneshwar et al, 2002;Khan et al, 2007Khan et al, , 2010Harvey et al, 2009;Richardson et al, 2009a;Zaidi et al, 2009). However, despite considerable promise microbial products for P mobilization have not had major application to broad-acre farming systems.…”
mentioning
confidence: 99%
“…Importance of IAA production in promoting root growth directly by stimulating plant cell elongation or indirectly by affecting bacterial ACC deaminase activity by PGPR has been greatly recognized (Kennedy et al 2004;Pedraza et al 2004). Similarly, role of phosphatesolubilizing bacteria in plant growth and development and the production of siderophores by PGPR especially under iron-limited conditions has been well documented (Ahmad et al 2008;Dimkpa et al 2008;Richardson et al 2009). One of the most PGP traits shown in many PGPR is to stimulate plant growth by the activity of ACC deaminase that promotes plant growth by decreasing plant ethylene levels.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these low concentrations in free Pi, soil may contain high levels of phosphorus that are not directly available to plant roots or microorganisms as P is combined either to cations to form mineral P or to carbon-containing compounds to form organic P. Given the Pi supply constraints in many soils, it is not surprising that plants have evolved strategies to acquire and/or efficiently use P. Plant adaptations that enhance the acquisition of inorganic Pi have been reviewed many times (e.g. Bucher 2007;Lambers et al 2008;Lynch and Brown 2008;Raghothama 1999;Richardson et al 2009;Vance et al 2003). Such adaptations include modifications to root structure and morphology, as well as biochemical (e.g.…”
Section: Introductionmentioning
confidence: 99%